1995
DOI: 10.1016/s1010-7940(05)80186-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining survival in resected N2 lung cancer

Abstract: This retrospective study was based on 237 patients with non-small cell lung cancer (NSCLC) and nodal N2 disease. All accessible mediastinal lymph nodes (LN) were removed and classified according to their anatomical location in LN chains. The pulmonary resections performed were: pneumonectomy (n = 187), lobectomy (n = 44) and segmentectomy (n = 4). There was solitary nodal chain involvement by metastasis in 141 cases, two chains in 72 cases and three or more in 24; "skip" metastases were present in 26.6%. N2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 22 publications
1
26
1
1
Order By: Relevance
“…3,4,6 However, some pN2 patients survived Ͼ 5 years. Such patients would be good candidates for surgical resection and they are expected to have a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6 However, some pN2 patients survived Ͼ 5 years. Such patients would be good candidates for surgical resection and they are expected to have a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was also asserted that no difference was identified between single N2 and multi N2 in terms of the survey. Riquet et al [13], also suggested that distribution of metastatic mediastinal limp nodes is not important for the prognosis. However, there are some studies reporting that prognosis is worse in patients with N2 positivity compared to patients with single N2 positivity [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that survival in between 19% and 45% in various series (2,4,7). Presence of multiple N2 metastases has been defined as a negatively influencing factor for prognosis in many series (4,12,13 (14). In staging study of IASLC, when relationship of lymph node involvement with survival was investigated, survival was determined to be much better in cases with single-region metastasis (median 35 months) compared to the ones with multiple-region metastasis (median 19 months) (15).…”
Section: Discussionmentioning
confidence: 99%